2019
DOI: 10.1016/j.celrep.2019.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Cilia Genes in Pancreatic Islets as a Risk Factor for Type 2 Diabetes in Mice and Humans

Abstract: Highlights d Differential expression of cilia-annotated genes in islets of diabetic mice and humans d Islets of control mice have more cilia, which disassemble under high glucose levels d Pathway enrichment analysis links affected cilia genes to cell division d Inhibition of KIF3A lowers islet cell replication in mice and humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Recent work has explored the link between ciliary dysfunction and diabetes (10,11,15,51). Here we show that primary cilia are required for multiple aspects of β-cell function, and we globally survey the cilia-dependent signaling network in islets.…”
Section: Discussionmentioning
confidence: 86%
“…Recent work has explored the link between ciliary dysfunction and diabetes (10,11,15,51). Here we show that primary cilia are required for multiple aspects of β-cell function, and we globally survey the cilia-dependent signaling network in islets.…”
Section: Discussionmentioning
confidence: 86%
“…NZO mice are a polygenic model for obesity and type 2 diabetes, developing metabolic stress-induced beta-cell failure under a specific high-caloric dietary regimen. This is composed of an initial carbohydrate-free, high-fat diet (-CH), triggering insulin resistance and obesity, followed by a carbohydrate-rich diet (+CH) that finally leads to hyperglycemia, beta-cell dysfunction and apoptosis [ [31] , [32] , [33] , [34] ]. By extending the metabolic challenge, the impact of an advanced age on pancreatic beta-cells under metabolic stress conditions was examined (study design illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse models prone to postprandial metabolic stress, such as NZO mice, mimic the human obesity-associated type 2 diabetes and were used in the present study. As previously described, young NZO mice exhibited obesity and insulin resistance when kept on a diet without carbohydrates, followed by depletion of insulin stores and a progressive loss of functional beta-cells in response to a carbohydrate intervention [ 27 , 31 , 32 , 34 , 42 ]. These mice showed distinct body weight gain due to ad libitum availability to the high-caloric carbohydrate-free diet.…”
Section: Discussionmentioning
confidence: 99%
“…Cilia are present, e.g., in endocrine β-cells, and it has been reported that cilia play a role in insulin signaling, insulin secretion, and β-cell function ( Gerdes et al, 2014 ). We recently reported that cilia-gene regulation has a strong impact on the presence and dynamics of cilia in islets which, in turn, determines diabetes susceptibility ( Kluth et al, 2019 ). However, as there are multiple transcript variants described for Ttc39a , which encode distinct isoforms, the specific role of the differently expressed isoform in the pathogenesis of diabetes in mice has to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-stimulated insulin secretion (GSIS) was performed, as described ( Kluth et al, 2019 ). Briefly, 30 isolated and 24 h recovered islets were equilibrated in Krebs-Ringer buffer for 30 min under low glucose (2.8 mM) conditions and transferred into perifusion chambers (PERI5-115, Biorep Technologies Inc., Miami Lakes, FL, United States) with a continuous flow of 100 μl/min.…”
Section: Methodsmentioning
confidence: 99%